1995
DOI: 10.3758/bf03213055
|View full text |Cite
|
Sign up to set email alerts
|

Speaking rate, voice-onset time, and quantity: The search for higher-order invariants for two Icelandic speech cues

Abstract: The temporal structure of speech has been shown to be highly variable. Speaking rate, stress, and other factors influence the duration of individual speech sounds. The highly elastic nature of speech would seem to pose a problem for the listener, especially with respect to the perception of temporal speech cues such as voice-onset time (VOT) and quantity: How does the listener disentangle those temporal changes whicqh are linguistically significant from those which are extrinsic to the linguistic message? This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 22 publications
6
65
0
Order By: Relevance
“…The best-fit regression lines for the aggregate data conform to previous observations showing substantial decreases in VOT for voiceless stops at fast rates of speech. That is, for /t/ VOT, Lane, Wozniak, Matthies, Svirsky, and Perkell (1995, note 1) calculated a regression slope of .14 from the data of Port and Rotunno (1979) and a slope of .17 from the data of Pind (1995) for Icelandic. These estimates approach the .15 slope observed in the present data (on the method used to calculate slopes and intercepts, see Kleinbaum, Kupper, & Muller, 1988).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The best-fit regression lines for the aggregate data conform to previous observations showing substantial decreases in VOT for voiceless stops at fast rates of speech. That is, for /t/ VOT, Lane, Wozniak, Matthies, Svirsky, and Perkell (1995, note 1) calculated a regression slope of .14 from the data of Port and Rotunno (1979) and a slope of .17 from the data of Pind (1995) for Icelandic. These estimates approach the .15 slope observed in the present data (on the method used to calculate slopes and intercepts, see Kleinbaum, Kupper, & Muller, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…For example, some authors see that an intrinsic timing view posits that VOT and syllable duration change with speaking rate "in such a way that this functional relation, or higher-order property, remains invariant" (Wayland et al, 1994(Wayland et al, , p. 2699. Because of the failure to find temporal constants in speech, relativetiming hypotheses have been largely dismissed (see the comments of Pind, 1995). There is substantial evidence that timing relations involving such aspects as VOT or formant transitions are not constant (e.g., Kessinger & Blumstein, 1998;Port, 1981;Volaitis & Miller, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For fortis stops in this study, there was a slope of .05ms VOT/ms word length. However, in the study by Magloire and Green (1999), English had a slope of .27ms VOT/ms word length, Pind (1995) reported a slope of .15ms VOT/ms word length for Icelandic aspirated stops, and Beckman et al (2011) reported a slope of .10 ms VOT/ms word length for aspirated Swedish stops. There was a slope of -.13ms VOT/ms word length for lenis stops in this study, compared to a slope of -.45ms VOT/ms for Spanish prevoiced stops (Magloire & Green 1999) and -.27ms VOT/ms for Swedish prevoiced stops (Beckman et al 2011).…”
Section: Languagementioning
confidence: 93%
“…Rate Effects. Previous research into the effect of speaking rate on VOT durations (e.g., Miller, Green, & Reeves 1986, Pind 1995, Allen & Miller 1999 show that in word-initial stop contrasts, VOT increases in the phonologically specified category as speaking rate decreases, while the unspecified category exhibits little change. Thus, in languages which contrast prevoiced stops with short-lag stops, such as Spanish (Table 3), prevoicing increases in slower speech and decreases in faster speech while short-lag VOT shows little difference.…”
Section: Short-lag Vot (Voiceless Unaspirated)mentioning
confidence: 99%